Educação e Saúde: a escola como lócus de higiene no Ceará (1930 - 1960) - Lima, Ana Michele da Silva (2013)
This research aims to study the School Hygiene in the period from 1930 to 1960, investigating memory learning environment, reliving conceptions and representations of hygiene and that environment, from the historical changes of concepts related to education, pedagogy , school and childhood itself. Considering the history of education in a given period, in a macro to micro perspective, proposals and impositions made from medical-school interventions and changes occasioned by these structure of Public Instruction in Ceará. Stressing here as justification for the choice of dating, setting a period of continuous changes in political, economic and cultural locus of several representative of the population. The analysis in the official documentation, and in magazines is a quest to review how physicians, institutions and education professionals in advanced studies and interventions of hygienic problems in the state, but mostly in Fortaleza. Such interventions were legitimized from conceptions hygienists and civilizing where the school was half disseminator and trainer of men useful, capable and aware of health issues in the contemporary city. In this sense to analyze concepts and representations around what is health, illness, health and education, and how those meanings were manipulative and have proposed coordinating a whole social restructuring is necessary. We intend to verify the establishment of a link between home, school and local public health by the authorities, aimed at re-education that tried to distance the charges given by the codes of posture. The quest to make the measures not rules, but habits, as far as possible, to all, reflecting changes in the educational structure from a physical perspective, the pedagogical issues to children and their own teacher training, promoting and revealing, so control strategies and organization of the city.